THE INFLUENCE OF FINANCIAL PERFORMANCE ON STOCK PRICE AROUND PUBLICATION DATE OF FINANCIAL STATEMENTS (A STUDY IN FOOD AND BEVERAGES COMPANIES LISTED ON BEI) - Alep Pradipta Abimantrana; Noval Adib (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Financial performance become the important factor which attract the investor in buying stock. One thing that is considered is the stock price because it can be used by the investor to measure the company performance. Before invest their money, investor should be analyse the company performance so investor can predict their return in the future. The research is aimed at testing the influence of ROI, ROE, DER, CR, NPM, PBV and EPS toward stock price to food and beverage companies which are listed in LQ-45 at Indonesia Stock Exchange in the period of 2010-2012. This research applies purposive sampling technique with 15 samples of companies. Multiple regressions are technical analysis method applied.Key Words : Stock’s Price, ROI, ROE, DER, CR, NPM, PBV and EPS LQ45, Analysis Financial Ratio